نظام جديد لتقنية اندماج المناطق في التحليل بالحقن الجرياني المستمر واستخدام مطياف مصنع محليا لتقدير عقار الباراسيتامول - ألبدري, شروق بدري سلمان; البياتي, يحيى كمال خليل (Al-Nahrain Journal of Science, 2018)
The unit is designed IT system integration areas in flow injection analysis together with the device careful photometer and that means measuring the complex color when a wavelength of 508 nm. Estimation method was used paracetamol drug through drug paracetamol oxidation using iron (III) converted into iron (II) and the interaction of iron (II) with reagent 1:10- Phenanthroline and using a buffer solution has been studying the chemical and physical variables to get the best results. Calibration curve is subject to the law of Bear - Lambert within the range (0.3-1.2) m